The effect of social media marketing on buying interest MS Glow skincare on DP3AKB employees in Serang City - Nisa, Khaerun; Divania, Yesika; Ziddan, Irham; Wahyudi, Wahyudi (Institute of Computer Science (IOCS), 2024)
This study aims to determine the effect of Social Media Marketing on MS Glow skincare buyinginterest in social media users in Serang City. The method in this study uses quantitative methods while collecting data using questionnaires that are directly distributed to respondents; the population in this study was 90 employees while sampling specific criteria including skincare buyers and Ms Glow skincare users at DP3AKB, resulting in a total of 79 respondents. The data analysis technique used is multiple regression analysis, followed by hypothesis testing using SPSS. This study also aims to prove the amount of influence social media marketing has on buying interest. The results obtained based on field findings as well as the results of the calculation, namely on the Effect of Social Media Marketing on Buying Interest in MS Glow Skincare on DP3AKB Employees in Serang City, that Social Media Marketing has a positive and significant effect on buying interest. This is indicated by a significance level of 0.000 <0.05. So H0 is rejected, and H1 is accepted, meaning that the social media marketing variable positively and significantly affects buying interest